2015
DOI: 10.1080/19443994.2014.960462
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide nanosheet: preparation and dye removal from binary system colored wastewater

Abstract: In this paper, graphene oxide (GO) was prepared from graphite and used as an adsorbent to remove cationic dyes from single and binary systems of colored wastewater. The GO was prepared by Hummer method and characterized using Fourier transform infrared, scanning electron microscopy, and X-ray diffraction. Basic blue 41 (BB41), basic red 18 (BR18), and basic red 46 (BR46) were used as model dyes. It was found that the adsorption of dyes on GO followed the Langmuir isotherm and the pseudo-second-order kinetics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…3. It can be clearly observed that the surface of rGO comprises crumpled and corrugated sheets which are both intrinsic properties of graphenic sheets [32][33][34]. From Fig.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…3. It can be clearly observed that the surface of rGO comprises crumpled and corrugated sheets which are both intrinsic properties of graphenic sheets [32][33][34]. From Fig.…”
Section: Resultsmentioning
confidence: 86%
“…2. For GO, the bands at 3419, 1729, 1620, 1222 and 1051 cm -1 are attributed to OH stretching, -C=O stretching (COOH group), C=C stretching (aromatic rings), C-O stretching (COOH group), and C-O-C stretching (epoxy group), respectively [34]. On the other hand, rGO upon hydrothermal treatment loses a large amount of oxygen functional groups, thus decreasing the intensities of the rGO bands associated with oxygen functional groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the maximum adsorption capacity and the main adsorption factors of the developed NOAC-based batch adsorption method with the other published adsorption methods for the removal of BR46 and BY13 dyes from single and binary systems 2,14,[22][23][24][25][26][27] were reported in Table V. Obviously, the adsorption capacity of NOAC used in this study is significantly high for single and binary systems.…”
Section: Comparison Of the Developed Noac-based Adsorption Methods Witmentioning
confidence: 94%
“…With the high aspect ratio, thin graphene sheets typically possess high specific surface area, allowing a large number of sites for interaction with other materials. Among graphene‐related materials, reduced graphene oxide and, especially, GO were used as dye adsorbents or incorporated into polymer matrices for enhancement of the dye adsorption performance of the polymers …”
Section: Introductionmentioning
confidence: 99%